LINGUISTIC FEATURES OF AUTHORIAL VOICE IN SCIENTIFIC DISCOURSE - Abdug‘aniyeva Zebuniso Abduhafizovna (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This article explores how linguistic features contribute to the construction of authorial voice in scientific discourse. Drawing upon theoretical frameworks and empirical studies, it examines how voice is realized through stance, hedges, self-mention and engagement. The article highlights the challenges faced by second language (L2) writers in projecting voice and proposes pedagogical strategies to support their development. Through a critical review of literature, the study argues that voice is not merely a stylistic choice but a rhetorical and epistemological necessity in scientific communication.